Pengaruh pemupukan P dan populasi jagung dengan tumpang sari kedelai pada budidaya jenuh air di lahan pasang surut - Faadhilah, Fajar; Lubis, Iskandar; Ghulamahdi, Munif (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Soybean and corn are the main food crops in Indonesia after rice. Currently to fill the needs of national soybeans and corn obtained through imports. That was due to the low productivity of soybeasn and corn in Indonesia compared to other countries like as the United States and China. Iimproving the productivity of corn and soybean is by regulating plant population and fertilizing. The purpose of this research was to determine the effect of P fertilizing and corn population on soybean and corn intercropping in tidal swamps. This research was in March to August 2019 in Karyabakti, Rantau Rasau District, Tanjung Jabung Timur Regency, Jambi Province. The tidal swamps type used was type B. The study was conducted using two factors i.e P fertilization (0 kg P2O5 ha-1, 46 kg P2O5 ha-1, 92 kg P2O5 ha-1, 138 kg P2O5 ha-1) and population maize (50,000, 63,000 and 73,000 plants ha-1). The intercropping system showed the highest results in a population of 63,000 maize ha-1 plants with a fertilizer dosage of P 46 kg P2O5 ha-1. Land equality ratio highest 2.3 showed that intercropping systems were 130% more effective than monoculture planting.